Programming Perl - Wall, Larry (Nutshell handbook., 1996)
If Perl itself is the first legend of Larry Wall, this book - affectionately known everywhere as The Camel Book - is the second. If you buy only one book about Perl, no one in the Perl community will question your judgment in buying this one. Contents include an extensive overview of the language and its syntax; a complete reference for all Perl functions, operators, and standard library modules; an explanation of Perl references and complex data structures; a detailed.